2014
DOI: 10.5603/kp.a2013.0086
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum resistin levels in patients with acute myocardial infarction

Abstract: Serum resistin level was increased in patients with AMI and constituted a risk factor for MACE in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Montazerifar et al [17] has found association between high serum leptin levels (another adipokine) and CAD, but there was no significant serum resistin elevation in CAD patients in their study in contrast to previous studies A study by Lee et al showed that high serum resistin levels were dependent predictors for all-cause mortality in patients with AMI [18]. In contrast, Erer et al showed the association of high baseline resistin levels with an increased risk of MACE and resistin was found to be an independent risk factor for predicting MACE in patients with AMI [19]. In a study, systemic review and meta-analysis, Fontana et al analyzed data from Gargano Heart Study (GHS) which was prospective in nature, to investigate the association between resistin and both all cause and cardiovascular (CV) mortality risk [20] [21].…”
Section: U Y Sinan Et Al World Journal Of Cardiovascular Diseasescontrasting
confidence: 54%
“…Montazerifar et al [17] has found association between high serum leptin levels (another adipokine) and CAD, but there was no significant serum resistin elevation in CAD patients in their study in contrast to previous studies A study by Lee et al showed that high serum resistin levels were dependent predictors for all-cause mortality in patients with AMI [18]. In contrast, Erer et al showed the association of high baseline resistin levels with an increased risk of MACE and resistin was found to be an independent risk factor for predicting MACE in patients with AMI [19]. In a study, systemic review and meta-analysis, Fontana et al analyzed data from Gargano Heart Study (GHS) which was prospective in nature, to investigate the association between resistin and both all cause and cardiovascular (CV) mortality risk [20] [21].…”
Section: U Y Sinan Et Al World Journal Of Cardiovascular Diseasescontrasting
confidence: 54%
“…The association of resistin with heart failure persisted after adjustment for established heart failure risk factors, obesity, markers of insulin resistance and inflammation, and concentrations of NT-proBNP, and after exclusion of prevalent and incident CHD. Erer et al 33 concluded that serum resistin concentration was elevated in patients with acute STEMI (sustained ST segment elevation of myocardial infarction), and this increase was more obvious in patients with T2DM than in those without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Erer HB [ 8 ] reported that serum resistin levels were similar in patients with STEMI and NSTEMI. Canga et al [ 32 ] demonstrated a significant increase of serum resistin levels in patients with slow coronary flow compared to patients with normal coronary flow.…”
Section: Discussionmentioning
confidence: 99%